Export Strategy Development in Micro and Small Enterprises of The Craft Sector in Central Java - Karsinah Karsinah; Purbayu Budi Santosa; Deden Dinar Iskandar (Economics Development Analysis Journal, 2025)
This study examines which factors most strongly drive export participation among craft-sector micro and small enterprises (MSEs) in Central Java. Focusing on batik, furniture, and leather products, we highlight a capability-first perspective that has been underexplored in this context. Using a survey of craft MSEs analyzed with logistic regression, we compare the effects of human capital (export knowledge and skills) with commonly cited enablers such as capital and government assistance. The results show that export knowledge and skills consistently predict export participation, whereas financial inputs and generic assistance are not decisive once capabilities are considered. These findings suggest that policies and firm strategies should prioritize practical export know-how, skills development, and market-readiness over undifferentiated financing. The study contributes evidence from Indonesia’s craft sector that human capital is the primary lever for scaling MSEs to international markets. The skills possessed in the Craft sector in Central Java regarding exports have a positive influence on their performance with a coefficient value of 5.76; this indicates that if the skills of MSEs in the Craft sector in Central Java increase by 1%, it will increase MSEs performance by 5.76%.